A stone in Spain's shoe : the search for a solution to the problem of Gibraltar - Gold, Peter (Liverpool University Press, 1994)
A detailed analysis of the attempt by Britain and Spain since 1980 to solve their dispute over the future of Gibralter, the last-remaining colony in Europe. Using Spanish as well as British sources, the book examines the events which have taken place following the signing of the Lisbon Agreement.